Gardening cyberspace—social media and hybrid spaces in the creation of food citizenship in the Bristol city-region, UK. (3rd October 2019) - Reed, Matt; Keech, Daniel
Abstract: This paper conducts a detailed analysis of urban food and online networks in Bristol, UK. In particular, it examines social media postings of grass-roots food networks. Qualitative research identifies and analyses five core themes, from which two dominant discourses emerge. Analysis reinforces the multifunctional nature of city food but moves beyond dominant scholarly pre-occupations with nutrition and physical resources. Instead, the paper positions social and symbolic aspects as equal components within the convening power of food. To date, social media has been neglected in urban food research, although this is a space as well-tended and structured as the physical spaces it augments. The paper finds a relationship of limited collaboration between the grass-roots networks and the city council. While the former are dynamic and networked, the council adheres to a linear policy process that limits the scope of citizenship. The relationships examined here indicate implications for urban planning processes.